Complex Analysis 2: Riemann Surfaces, Several Complex Variables, Abelian Functions, Higher Modular Functions - Freitag, Eberhard (Springer-Verlag Berlin Heidelberg, 2011)
Chapter I. Riemann Surfaces -- Chapter II. Harmonic Functions on Riemann Surfaces -- Chapter III. Uniformization -- Chapter IV. Compact Riemann Surfaces -- Appendices to Chapter IV -- Chapter V. Analytic Functions of Several Complex Variables -- Chapter V. Analytic Functions of Several Complex Variable -- Chapter VI. Abelian Functions -- Chapter VII. Modular Forms of Several Variables -- Chapter VIII. Appendix: Algebraic Tools -- References -- Index.
Includes bibliographical references and index
Keywords: Funktionstheorie